Strategi Pengembangan Arsitektur dalam Penyediaan Ruang Homestay di Kampung Homestay Ngaran II Borobudur, Magelang - Shafa Amalia Sukowati; Dwita Hadi Rahmi (Universitas Dwijendra, 2025)
Borobudur is one of Indonesia's top tourist destinations, attracting millions of visitors each year. As a UNESCO World Heritage Site, Borobudur Temple plays a significant role in driving the growth of the tourism sector and creating various economic opportunities for the local community. One of the emerging business ventures in the area is community-based homestays, where residents offer accommodations to tourists by utilizing available land around their homes. This initiative reflects the community’s adaptation to the rapid development of Borobudur’s tourism industry. However, it also raises concerns about architectural development strategies in homestay design while maintaining the traditional characteristics of village houses. This study aims to: (1) identify architectural development strategies in homestay design and (2) determine the key factors influencing these strategies. The research focuses on four homestays in Kampung Homestay Ngaran II, Borobudur. Findings reveal that local communities have adapted to tourism opportunities and demands by providing homestay accommodations without compromising the distinctive features of traditional village houses. Homestays are typically built within the same yard as the main house, carefully designed to balance privacy for both the homeowners and guests while maximizing land use efficiency. The main factors influencing homestay development include land utilization, economic needs, and the tourism potential of the Borobudur area.